1982
DOI: 10.1111/j.1532-5415.1982.tb05620.x
|View full text |Cite
|
Sign up to set email alerts
|

Female Preponderance in Diuretic‐associated Hypokalemia

Abstract: A retrospective review of the medical records of 161 geriatric nursing-home patients receiving diuretics alone or in combination with potassium supplements or potassium sparing-diuretics revealed a 13.7 per cent overall prevalence of hypokalemia. The prevalence of hypokalemia in patients receiving diuretics alone, diuretics with potassium supplements, and potassium-sparing diuretics with kaliuretic diuretics were similar. However, there was a significantly higher prevalence of hypokalemia in women (16.4 per ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…These results confirm previous reports (Clark et al, 1982;Krakauer & Lauritzen, 1978;Morgan, 1981) that women are more likely than men to have hypokalaemia when treated with diuretics, but in addition show that this phenomenon is not confined to elderly patients and, unlike earlier studies, cannot be explained by differences, between the sexes, in the type and dose of diuretic, the concurrent use of other antihypertensive drugs, and the presence of heart failure. Serum potassium (mmol/1) Figure 1 Distribution of serum potassium in 102 women (O) and 91 men (Li) taking bendrofluazide 5 mg daily for hypertension.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results confirm previous reports (Clark et al, 1982;Krakauer & Lauritzen, 1978;Morgan, 1981) that women are more likely than men to have hypokalaemia when treated with diuretics, but in addition show that this phenomenon is not confined to elderly patients and, unlike earlier studies, cannot be explained by differences, between the sexes, in the type and dose of diuretic, the concurrent use of other antihypertensive drugs, and the presence of heart failure. Serum potassium (mmol/1) Figure 1 Distribution of serum potassium in 102 women (O) and 91 men (Li) taking bendrofluazide 5 mg daily for hypertension.…”
Section: Discussionsupporting
confidence: 91%
“…It has recently been reported that hypokalaemia may not be a significant problem in men taking diuretics (Clark et al, 1982;Krakauer & Lauritzen, 1978;Morgan, 1981) and suggested that monitoring of serum potassium and the use of prophylaxis against hypokalaemia need only be considered for women (Morgan, 1981). However, the three studies cited involved only elderly patients and failed to take sufficient account of those factors known to affect serum potassium, including the use of potassium supplements and potassium sparing drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Lower plasma potassium concentrations in women compared to men have been reported in previous human and animal studies 64-66 and attributed to estrogen effects, enhancing the action of mineralcorticoids on the kidney and increasing β 2 adrenoreceptor density, affinity or G protein coupling to adenylate cyclase in skeletal muscle and red blood cells thus causing an intracellular influx of potassium into the cells. 66, 67 …”
Section: Discussionmentioning
confidence: 73%